ANALISIS KELAYAKAN INVESTASI PENGEMBANGAN JARINGAN AIR BERSIH DI PERUMAHAN GRAHA INDAH TAMBAKRIGADUNG KECAMATAN TIKUNG KABUPATEN LAMONGAN (Jurnal Spesialis Teknik Sipil (JSpTS), 2021)
Graha Indah housing is one of the areas in Tikung District, Lamongan Regency which has less water availability. The desire of residents of Graha Indah housing to get clean water supply from PDAM is quite high. In the implementation of the clean water supply system in Graha Indah Housing, it has not been able to run optimally. From the results of planning calculations, it can be seen that the service needs of clean water in Graha Indah Housing in the projected year 2034 the minimum required discharge is 0.02707 m3/sec. From the results of the calculation of the cost of developing the pipeline network is Rp. 3,295,526,607. From the results of the calculation of the Net Cash Flow NPV value is Rp. 2,291,168,801. BEP shows that the profit or profit in year 9 is Rp. 123,545,805, and in the 15th year, namely in 2034 Rp. 4,193,389,172. The IRR value is 14.3%, the minimum expected interest rate is 13%, so the investment in developing clean water networks is feasible.